Association between alcohol consumption and risk of type 2 diabetes in Japan: a population-base longitudinal cohort study - Yuan-Zhe Huang; Fang Luo; Xiong Ran; Jian Yang; Min Gu; Shao-Quan Zhou (Scientific Reports)
Abstract Heavy alcohol consumption is a known risk factor for type 2 diabetes (T2D), However, the moderating effect of fasting plasma glucose (FPG) levels remains unclear. This study explores the relationship between alcohol intake and T2D risk across FPG strata in a Japanese cohort. Data from 15,453 participants in the NAGALA cohort were analyzed over 5.4 years. Baseline assessments included alcohol consumption and FPG, categorizing individuals into elevated FPG (EFPG, 100–125 mg/dL) and normal FPG (NFPG, < 100 mg/dL). Cox proportional hazards regression assessed alcohol intake levels and T2D risk, stratified by FPG. Among EFPG individuals, heavy drinkers (Men > 280 g/week, Women > 140 g/week) had an 88% increased T2D risk (HR 1.88, 95% CI 1.24–2.84). Conversely, in NFPG, heavy alcohol intake did not significantly affect T2D risk (HR 1.10, 95% CI 0.48–2.53). Men with EFPG and heavy alcohol intake had an HR of 1.83 (95% CI 1.08–3.08), supported by propensity score matching (HR 1.94, 95% CI 1.13–3.34). No significant relationships were found in NFPG. Heavy alcohol consumption significantly raises T2D risk in Japanese men with EFPG but not in women or those with NFPG. Further studies are warranted for validation and gender-specific insights.